Constructing intellectual property / Alexandra George. - George, Alexandra (Cambridge University Press, 2012)
What is 'intellectual property'? This book examines the way in which this important area of law is constructed by the legal system. It argues that intellectual property is a body of rules, created by the legal system, that regulate the documented forms of abstract objects, which are also defined into existence by the legal system. Intellectual property law thus constructs its own objects of regulation and it does so through the application of a collection of core concepts. By analyzing the metaphysical structure of intellectual property law and the concepts the legal system uses to construct 'intellectual property', the book sheds new light on the nature of this fascinating area of law. It explains anomalies between social and intellectual property uses of concepts such as authorship - here dubbed 'creatorship' - and originality and it helps to explain the role of intellectual property from a structural (rather than the traditional normative) perspective.